2016
DOI: 10.4269/ajtmh.15-0461
|View full text |Cite
|
Sign up to set email alerts
|

A Health Care Worker with Ebola Virus Disease and Adverse Prognostic Factors Treated in Sierra Leone

Abstract: We describe the management of a Sierra Leonean health care worker with severe Ebola virus disease complicated by diarrhea, significant electrolyte disturbances, and falciparum malaria coinfection. With additional resources and staffing, high quality care can be provided to patients with Ebola infection and adverse prognostic factors in west Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Granulocytosis, thrombocytopenia, and elevated BUN and CRE levels are common characteristics of severe disease caused by RVFV and other pathogenic viruses, such as Ebola virus and Crimean-Congo hemorrhagic fever (CCHF) virus (38)(39)(40). Serum samples from 26 patients from the 2000 outbreak of RVFV in Saudi Arabia showed increased WBC and decreased platelets in fatal cases relative to levels in survivors (6,41).…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytosis, thrombocytopenia, and elevated BUN and CRE levels are common characteristics of severe disease caused by RVFV and other pathogenic viruses, such as Ebola virus and Crimean-Congo hemorrhagic fever (CCHF) virus (38)(39)(40). Serum samples from 26 patients from the 2000 outbreak of RVFV in Saudi Arabia showed increased WBC and decreased platelets in fatal cases relative to levels in survivors (6,41).…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite the prevalence of malaria in countries at risk for EVD outbreaks, little data exist pertaining to Ebola virus and malaria parasite co-infection. One case report 4 describes a health-care worker co-infected with Ebola virus and Plasmodium falciparum with multiorgan failure, and a retrospective study 5 of patients in Liberia showed a prevalence of co-infection of 15%. The antimalarial amodiaquine might have activity against Ebola virus.…”
Section: Introductionmentioning
confidence: 99%
“…The level of sophistication of these interventions varies from basic oral rehydration therapy without laboratory investigations in the most resource poor settings, through to invasive fluid, electrolyte and blood product management, mechanical ventilation, and haemodialysis with full laboratory and radiology support in intensive care units in developed countries [42]. Even within countries most affected by EVD, the level of supportive care varied widely [59,60]. Whether increasing sophistication of supportive care is associated with improved outcomes is not proven, however, one could not dispute this intuitively.…”
Section: Supportive Carementioning
confidence: 99%